Landscapes without landscape architects. The ecological beauty of informal urban landscapes - Chiara Catalano; Thomas E. Hauck; Susann Ahn; Salvatore Pasta (Agathón)
Regarding the maintenance of urban green infrastructure, most stakeholders prefer achieving an oversimplified aesthetic archetype of cleanliness and order at the cost of high maintenance, whilst landscape architects try to reproduce islands of near-natural vegetation even where the environmental factors typical of urban areas do not allow it. In the long term, the struggle between these two opposite ways of conceiving the look and the role of green infrastructure appears pointless: in the end, what decides the identity of most urban green infrastructure is the ‘vegetation by use’, that is, the daily people’s use of these spaces (whether accessible). By analysing the aesthetic value, the species composition, and the ecological meaning of the vegetation of some roadside habitats close to the city of Catania (Sicily), the Authors shed light on the possibility of enjoying low-cost, biodiverse and beautiful seasonally green areas.